Pelatihan Manajemen Keuangan dan Administrasi BUMDES untuk peningkatan daya saing BUMDES ( Badan Usaha Milik Desa ) Menuju Desa Mandiri pada BUMDES Puloniti, Kabupaten Mojokerto - Ratnawati, Dyah; Syaiful Akbar, Fajar; Khanida, Marisha (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of the economic world in Indonesia in general, in Mojokerto in particular, has made various business actors compete in improving the performance of their companies through product competitiveness and improving the company's operational systems themselves, based on research conducted by the UNIM Accounting Study Program Community Service Team in collaboration with the UPN Accounting Service Team " Veterans" of East Java proposed training related to the Implementation of Financial Management and Administration of BUMDES for BUMDES of Puloniti Village which is engaged in general trade and services and was approved to conduct training on 15 – 16 May 2023 offline or face to face with the output of the training, namely BUMDES be able to make controlled planning regarding Village Business Entity Finances adjusted to the BUMDES Restra into the administration of BUMDES governance, and this training is ongoing where the UNIM Accounting Study Program Community Service Team and the UPN "Veteran" East Java Accounting Study Program Community Service Team will continue to monitor and assist BUMDES Puloniti Village in overall financial and operational management of BUMDES.